2015
DOI: 10.1097/rlu.0000000000000828
|View full text |Cite
|
Sign up to set email alerts
|

Variability of Hepatic 18F-FDG Uptake at Interim PET in Patients With Hodgkin Lymphoma

Abstract: At interim PET in patients with HL, liver SUVmean depends on BMI and sex, but not liver SULmean. Furthermore, our study, conducted with standard clinical procedure, also confirmed the high range of liver uptake values from one patient to another. Caution is required when using liver SUV as reference in patients with high BMI. Intrapatient fluctuation in liver SUVmean should also be expected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 26 publications
2
5
1
Order By: Relevance
“…The study showing a positive relationship between steatosis and SUV max did not actually take into account patients BMI, and; therefore, these results were certainly biased [ 15 ]. In our study, BMI and BGL appeared to be statistically different between steatotic and non-steatotic groups of patients whereas other parameters described as potentially affecting hepatic uptake {age, sex, treatment, time course of treatment [ 14 , 19 21 ]} were not. Concerning BGL, a proportional relationship with 18 F–FDG liver uptake has been shown, even for blood glucose in line with EANM recommendations [ 22 ].…”
Section: Discussioncontrasting
confidence: 64%
“…The study showing a positive relationship between steatosis and SUV max did not actually take into account patients BMI, and; therefore, these results were certainly biased [ 15 ]. In our study, BMI and BGL appeared to be statistically different between steatotic and non-steatotic groups of patients whereas other parameters described as potentially affecting hepatic uptake {age, sex, treatment, time course of treatment [ 14 , 19 21 ]} were not. Concerning BGL, a proportional relationship with 18 F–FDG liver uptake has been shown, even for blood glucose in line with EANM recommendations [ 22 ].…”
Section: Discussioncontrasting
confidence: 64%
“…It has been noticed that the comparability of quantitative values, calculated under different reconstruction methods, may be limited [13,14]. It should also be taken into account that the liver SUV depends on gender and body mass index, but not the liver standardized uptake value corrected for lean body mass (SUL) [15]. One proposal for tackling the problem Table 2 Maximal standard uptake values corrected for body weight (SUVmax) and for lean body mass (SULmax) as well as the peak SUV and SUL (SUVpeak, SULpeak) were measured in the single hottest lesion in the lung after OSEM reconstruction and UHD reconstruction for each patient.…”
Section: Introductionmentioning
confidence: 99%
“…Each facility has its own policy regarding the need for glucose level testing prior to PET CT examination, and some facilities do not routinely perform glucose level testing prior to PET CT scans, unless the patients have diabetes or feel unwell. This practice is based on several published reports that have demonstrated that the impact of glucose levels on SUVs in most organs is negligible, and delaying the scan might harm the patient [20][21][22][23]. Nonetheless, among the patients for whom glucose data were available, there was no difference in the mean glucose levels between the steroid-treated and steroidnaïve groups.…”
Section: Discussionmentioning
confidence: 99%